Adoption and impact of quick response manufacturing across industry sector - N., Nelfiyanti; Ahmad Shah Hizam, Md Yasir; Nik Mohd Zuki, Nik Mohamed; Mohd Fadzil Ali, Ahmad (Springer International Publishing, 2025)
Quick response manufacturing (QRM) is a strategic manufacturing approach aimed at reducing production cycle times to enhance operational efficiency and competitiveness. Industries today face persistent challenges, such as delayed product deliveries, high operating costs, and inefficiencies that hinder productivity and quality. While numerous studies have highlighted the theoretical benefits of QRM, there remains a lack of consolidated evidence on its practical impact across multiple industry sectors. Specifically, there is limited comparative analysis that synthesizes QRM outcomes in diverse contexts, such as precision manufacturing, textiles, and small and medium industries (SMI). This research gap hinders a broader understanding of QRM’s cross-sector applicability and its tangible contributions to production performance. To address this gap, this study evaluates the adoption and impact of QRM across various industry sectors through a comprehensive literature review, analyzing 70 academic articles and industry reports. The research focuses on three critical areas: (1) efficiency in production and delivery, (2) cost reduction, and (3) enhancement of product quality and quantity. Data was sourced from peer-reviewed academic journals, industry case studies, and relevant research reports. The findings reveal that QRM significantly improves on-time delivery by 45% and reduces production backlog by 50%. Additionally, QRM lowers warehousing and inventory costs by 35% and minimizes production downtime costs by 40%. Product quality and quantity improvements include a 30% reduction in defects and a 25% increase in output. This study fills the existing research gap by providing a sector-spanning evaluation of QRM’s effectiveness and concludes that QRM is a highly effective strategy for optimizing manufacturing efficiency, enhancing supply chain operations, and reducing operational costs. It offers valuable insights for industry stakeholders seeking data-driven justifications for adopting QRM, especially in environments where responsiveness and efficiency are critical for competitiveness.